Pengaruh Kemudahan Penggunaan, Manfaat, Keamanan Dan Promosi Terhadap Keputusan Penggunaan E-Wallet Ovo - Dwi Yuliyanti Astuti; Mahmud Mahmud (Jurnal Mirai Management, 2023)
This study aims to analyze the effect of ease of use, benefits, security and promotion on the decision to use OVO e-wallet. The population in this study are consumers of E-wallet users who have made transactions on OVO at least 2 times with an age range of